A Case of Turmeric-Induced Liver Injury - Nadia Smati; Crystal Xue; Manasa Vallabhaneni; Ibironke Oduyebo (Annals of Internal Medicine: Clinical Cases)
Turmeric spice and its active ingredient, curcumin, are becoming more commonly used, despite a simultaneous increase in reports of turmeric-induced hepatotoxicity. Our report demonstrates an additional case of turmeric-induced liver injury with concurrent ingestion of bioavailability-increasing substances. Despite known underreporting, a significant proportion of documented drug-induced liver injuries are secondary to herbal and dietary supplements. There are also high variabilities in supplement dosage and delivery, as well as lack of regulation in the supplements industry. Our case highlights the importance of discussing supplement-specific medical histories and educating patient on the risks for unregulated supplement use.